The Cultural Role and Political Implications of Poland’s 1947 Shakespeare Festival - Krystyna Kujawińska Courtney (Text Matters, 2017)
Emerging from the atrocities of war, and still hoping to avert the results of the Yalta conference during which the countries of Central and South–Eastern Europe, including Poland, were “handed over” to Stalin, Poland’s 1947 Shakespeare theatre festival was a sign of courage and defiance. At the Festival 23 productions of 9 Shakespeare’s dramas were staged by theatres in 11 towns, with its finale in Warsaw. My paper will show that the Festival was an attempt to demonstrate both Polish cultural links with Europe, and to subvert Marxist ideology and Soviet culture.